Transport infrastructure and the environment: Sustainable mobility and urbanism - Robert Cervero (University of California, Institute of Urban and Regional Development (IURD), 2013)
The urban transportation sector's environmental, economic, and social footprint is immense and expanding. Many of the world's most vexing and pressing problems - fossil fuel dependency, global warming, poverty, and social exclusion - are inextricably tied to the transportation sector. Much of the blame for the transportation sector's inordinate environmental footprint lies in the increasing automobile-dependency of cities. Rapid motorization unavoidably shifts future travel from the most sustainable modes - public transport and non-motorized ones (walking and cycling) - to private vehicles. Despite growing concerns over energy futures, climate change, and access for the poor, public transport's market share of trips is expected to erode over the next decade in all world regions if past trends (in how ownership and usage of the private car is priced and public financial resources are spent on transport infrastructure) continue. A paradigm shift is needed in how we think about transportation and its relationship to the city. The integration of transport infrastructure and urban development must be elevated in importance. In many cities of the Global South, recent Bus Rapid Transit (BRT) investments provide an unprecedented opportunity to do just that. To date, however, BRT systems have failed to leverage compact, mixed-use development due not only to little strategic station-area planning but also factors like siting lines and stations in stagnant urban districts and busy roadway medians. BRT systems are being conceived and designed as mobility investments rather than city-shaping ones. Given that the majority of future urban growth worldwide will be in intermediate-size cities well-suited for BRT investments, the opportunities for making these not only mobility investments but cityshaping investments as well should not be squandered. Transit-oriented development is but one of a number of built forms that hold considerable promise toward placing cities of the Global South on more sustainable mobility and urbanization pathways.
Keywords: 330; Public Transport; Bus Rapid Transit; Land Use; Sustainability; Transit Oriented Development